2015
DOI: 10.4161/15384101.2014.994904
|View full text |Cite
|
Sign up to set email alerts
|

eIF2 kinases mediate β-lapachone toxicity in yeast and human cancer cells

Abstract: b-lapachone (b-lap) is a novel anticancer agent that selectively induces cell death in human cancer cells, by activation of the NQO1 NAD(P)H dehydrogenase and radical oxygen species (ROS) generation. We characterized the gene expression profile of budding yeast cells treated with b-lap using cDNA microarrays. Genes involved in tolerance to oxidative stress were differentially expressed in b-lap treated cells. b-lap treatment generated reactive oxygen species (ROS), which were efficiently blocked by dicoumarol,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Naphthoquinones present a chemical structure of naphthalene with two ketone groups at position C-1 and C-2 (1,2-naphthoquinones) or C-1 and C-4 (1,4-naphthoquinones) [ 9 ]. The considerable interest in these compounds is based on their pharmacological activities, especially as antimicrobial [ [8] , [9] , [10] , [11] ] and antitumor agents [ [12] , [13] , [14] , [15] ]. Most recently, 1,4-naphthoquinones, such as menadione (vitamin K3), have aroused a lot of interest due to relevant anticancer activity [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Naphthoquinones present a chemical structure of naphthalene with two ketone groups at position C-1 and C-2 (1,2-naphthoquinones) or C-1 and C-4 (1,4-naphthoquinones) [ 9 ]. The considerable interest in these compounds is based on their pharmacological activities, especially as antimicrobial [ [8] , [9] , [10] , [11] ] and antitumor agents [ [12] , [13] , [14] , [15] ]. Most recently, 1,4-naphthoquinones, such as menadione (vitamin K3), have aroused a lot of interest due to relevant anticancer activity [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Anaissi-Afonso et al [36] have also observed that βlap and derivatives at 10-100 μM exert their antifungal activity through oxidative stress and mitochondrial disfunction. On the other hand, Menacho-Márquez et al [37] observed that preincubation with dicoumarol did not affect the antifungal toxicity of β-lap, indicating that ROS production is not the mechanism responsible for the toxicity of β-lap against S. cerevisiae. In this study, it was observed that combining β-lap and fluconazole did not enhance ROS production.…”
Section: Discussionmentioning
confidence: 97%
“…The data indicated the mitochondrial electron transport chain, specifically respiratory complex I, to be a principal factor in redox activation of β-lap [10]. Although the main mechanism of cancer cell killing by β-lap is ROS-dependent, recent evidence suggested an alternative, ROS-independent, pathway for β-lap toxicity [11]. These results imply that chemotherapeutic quinones may react with multiple cellular constituents to promote cancer cell death, and the efficacy of NQO1-bioactivatable drugs may be improved by concomitant targeting of several cancer-specific metabolic pathways [6, 12].…”
Section: Introductionmentioning
confidence: 99%